Young adults' partner preferences and parents' in‐law preferences across generations, genders, and nations. (7th February 2020) - Locke, Kenneth D.; Mastor, Khairul A.; MacDonald, Geoff; Barni, Daniela; Morio, Hiroaki; Reyes, Jose Alberto S.; Vargas‐Flores, José de Jesús; Ibáñez‐Reyes, Joselina; Kamble, Shanmukh; Ortiz, Fernando A.
Abstract: To examine cultural, gender, and parent–child differences in partner preferences, in eight countries undergraduates ( n  = 2, 071) and their parents ( n  = 1, 851) ranked the desirability of qualities in someone the student might marry. Despite sizable cultural differences—especially between Southeast Asian and Western countries—participants generally ranked kind / understanding (reflecting interpersonal communion) highest, and intelligent and healthy (reflecting mental/physical agency) among the top four. Students valued exciting, attractive partners more and healthy, religious partners less than parents did; comparisons with rankings by youth in 1984 (i.e., from the parents' generation) suggested cohort effects cannot explain most parent–child disagreements . As evolutionary psychology predicts, participants prioritized wives' attractiveness and homemaker skills and husbands' education and breadwinner skills; but as sociocultural theory predicts, variations across countries/decades in gendered spousal/in‐law preferences mirrored socioeconomic gender differences. Collectively, the results suggest individuals consider their social roles/circumstances when envisioning their ideal spouse/in‐law, which has implications for how humans' partner‐appraisal capabilities evolved.